Safety nets for agriculture and nutrition - Gilligan, Daniel O. (International Food Policy Research Institute, 2019)
This chapter presents selected evidence on the impact of safety nets on agriculture and nutrition separately, examines trends in the development of more integrated programs, and outlines key areas of potential and challenges to better harnessing safety nets for agriculture and nutrition.